Nghiên cứu ảnh hưởng của sự dịch chuyển các chất lưu hóa đến quá trình lưu hóa blend cao su tự nhiên-cao su EPDM (CSTN/EPDM). Phần 1. Ảnh hưởng của chất xúc tiến đến quá trình lưu hóa - Hưng, Đặng Việt; Long, Uông Đình; Duy Linh, Nguyễn Phạm; Chương, Bùi (Vietnam Journal of Chemistry, 2016)
Effect of accelerator on the vulcanization parameters of natural rubber (NR) and ethylene-propylene diene rubber (EPDM) was studied. It was showed the variation in type and content of accelerators may lead to noticeable changes of vulcanization parameters of rubbers. The results of study of vulcanization curves of separate rubbers and their blends may be used for evaluation of migration and redistribution of accelerators in NR-EPDM blends. Keywords. Blend NR/EPDM, vulcanization parameters, natural rubber, EPDM rubber, accelerators